2022
DOI: 10.1021/acs.jpca.2c04462
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Reflection–Absorption Spectroscopy of α-Hydroxyacids at the Water–Air Interface

Abstract: Organic molecules, including α-hydroxyacids, are ubiquitous in the natural environment. Often found at water−air interfaces, organic molecules can alter the structure of the interface or participate in interfacial chemistry. Despite their prevalence in the environment, the structure and ordering of α-hydroxyacids have not been widely investigated at water−air interfaces, and the impact of the hydrophobic tail length on structure has not been explored. Here, for the first time, we use infrared reflection−absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 95 publications
1
40
0
Order By: Relevance
“…IR reflection–absorption spectra of α-keto acids at the air–water interface were obtained using a home-built IR-RAS setup and methodology as described previously. ,, Briefly, a PTFE trough from KSV-NIMA (14.5 cm × 7 cm × 0.5 cm) was optionally equipped with a Wilhelmy microbalance and Delrin barriers. The microbalance and barriers were used when studying insoluble molecules and were removed when studying soluble molecules.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…IR reflection–absorption spectra of α-keto acids at the air–water interface were obtained using a home-built IR-RAS setup and methodology as described previously. ,, Briefly, a PTFE trough from KSV-NIMA (14.5 cm × 7 cm × 0.5 cm) was optionally equipped with a Wilhelmy microbalance and Delrin barriers. The microbalance and barriers were used when studying insoluble molecules and were removed when studying soluble molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Air–water interfaces are ubiquitous in natural environments, both on the surface of oceans and on atmospheric aerosols. Recent studies have shown that the unique properties of these interfaces lead to morphological and chemical changes that are not fully understood. These interfaces concentrate and align organic material, and even small, soluble organic molecules partition preferentially to the water surface. , The resulting organic films at aqueous interfaces can control molecular transfer between the vapor and condensed phases, altering their optical properties and thereby affecting the earth’s radiative balance and other atmospheric processes. , Recent reports in the literature have repeatedly demonstrated enhanced reactivity and increased reaction rates in confined microenvironments (e.g., microdroplets, nanoemulsions, and aerosol), , highlighting the critical question of the role that the interface may play in these observed effects. In order to better understand how such aqueous interfaces may provide auspicious reaction environments, fundamental studies that explore the detailed surface behavior of model systems of organics are needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactions on surfaces are examined, including a kinetic and mechanistic study of gas–solid and gas-phase ozonolysis of nitrogen-containing alkenes, and the formation of organic nitrates in the heterogeneous reaction of α-pinene with mineral surfaces . Laboratory studies of the air–water interface demonstrate surface adsorption of H 2 O 2 , as well as determining the structure of hydroxy organic acids of varying size at the interface . Additional work addresses adsorption–desorption of semivolatile VOCs on mineral surfaces, and reactive uptake of HgO and a recently discovered dimethyl sulfide oxidation product (hydroperoxymethyl thioformate) on aerosols of various compositions. , The effects of aerosol properties on ice nucleation and on the partitioning of semivolatiles, , the effects of pH on organosulfate structures in the condensed phase, and the accessibility of various nanostructures for surfactants on atmospheric aerosol proxies are also reported.…”
mentioning
confidence: 99%